Effects of Covid 19 Pandemic on Tourism in Tanzania - Baraka, Godfrey (International Journal of Modern Hospitality and Tourism, 2023)
Purpose: The study sought to analyze the effects of Covid 19 pandemic on tourism in Tanzania. Methodology: The study adopted a desktop methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The results show that showed that The COVID-19 pandemic has caused significant disruptions in the global economy. By the end of the first quarter of 2020, the COVID-19 pandemic had brought international travel to an abrupt halt and significantly impacted the tourism industry. For many developed and developing countries, the tourism sector is a major source of employment, government revenue and foreign exchange earnings. Without this vital lifeline, many countries may experience a dramatic contraction in GDP and a rise in unemployment. Unique Contribution to Theory, Practice and Policy: Theory of planned behavior and evolution of value chain theory may be used to anchor future studies in the tourism sector. The study results will also benefit other stakeholders such as the policy makers as well as researchers and scholars from different parts of the world. The top management of tourism industries in the country will also use the study findings to improve health performance in all their activities and programs. The study recommends that the adoption of effective social protection development policies in the tourism sector will help to improve efficiency in their major operations and activities.